Development of an antibody-based colloidal gold immunochromatographic lateral flow strip test for natamycin in milk and yoghurt samples. Issue 6 (2nd November 2017) - Liu, Liqiang; Chen, Yanni; Song, Shanshan; Zheng, Qiankun; Wu, Xiaoling; Kuang, Hua
ABSTRACT: An immunochromatographic lateral flow strip test was developed for the detection of natamycin (Nata) residues in milk and cheese samples. Monoclonal antibody (mAb) against Nata was produced with a half maximal inhibitory concentration of 1.85 μg L −1 . MAb conjugated with gold nanoparticles was the detection reagent. Nata conjugated with ovalbumin via the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/ N -hydroxysuccinimide method immobilized on a nitrocellulose membrane was the capture reagent. This semi-quantitative method required only 15 min to complete. The optimum concentrations of coating antigen and mAb were 0.15 µg mL −1 and 0.2 µg mL −1, respectively. Based on an optical density scanner, the visual limit of detection of Nata was 5 μg L −1 and 10 μg kg −1 in milk and yoghurt samples, respectively.